Dynamics of superconformal axion: Quality and scalegenesis - Shota Nakagawa; Yuichiro Nakai; Masaki Yamada; Yufei Zhang (Physics Letters B, 2024)
We explore a dynamical mechanism to realize the emergence of a global U(1)PQ symmetry and its spontaneous breaking at an intermediate scale for an axion solution to the strong CP problem. Such a dynamics is provided by a new supersymmetric QCD near the middle of conformal window that couples to fields spontaneously breaking the U(1)PQ symmetry. A large anomalous dimension of the U(1)PQ breaking fields leads to the suppression of explicit U(1)PQ-violating higher dimensional operators. The U(1)PQ breaking vacuum is generated at a scale hierarchically smaller than the Planck scale by a non-perturbative effect. The U(1)PQ breaking drives the conformal breaking, and all the new quarks become massive. The axion potential is generated by the ordinary color SU(3)C effect as the U(1)PQ symmetry is only anomalous under the SU(3)C. The saxion direction is stabilized by supersymmetry breaking and cosmologically harmless.